Efeito da concentração de sólidos e de variáveis operacionais no desempenho de um hidrociclone concentrador - Gonçalves, Suélen Mara (2016)
The hydrocycloning operation has a goal to separate solid-liquid suspensions and liquid-liquid emulsions through the centrifugal force action. Hydrocyclones are equipment with reduced size and used in both clarification and thickening. This device is used in many areas, like petrochemical and minerals process, and accumulate advantages like versatility and low cost of maintenance. However, the demand to improve the process and to reduce the costs has motivated several studies of equipment optimization. The filtering hydrocyclone is a non-conventional equipment developed at FEQUI/UFU with objective to improve the hydrocycloning separation efficiency. The purpose of this study is to evaluate the operating conditions of feed concentration and underflow diameter on the performance of a filtering geometry optimized to minimization of energy costs. The filtration effect was investigated through the comparison between the performance of the Optimized Filtering Hydrocyclone (HCOF) and the Optimized Concentrator Hydrocyclone (HCO). Because of the resemblance of hydrocyclones performance, the filtration did not represent significant effect on the performance of the HCOF. It was found that in this geometry the decrease of the variable underflow diameter was very favorable to thickening operation. The suspension concentration of quartzite at 1.0% of solids in volume was increased about 42 times when the 3 mm underflow diameter was used. The increase on the feed solid percentage was good for decreasing the energy spent, so that a minimum number of Euler of 730 was achieved at CVA = 10.0%v. However, a greater amount of solids in suspension leads to a lower efficiency of the equipment. Therefore, to minimize the underflow-to-throughput ratio and keep a high efficiency level, it is indicated to work with dilute suspension (CVA = 1.0%) and 3 mm underflow diameter (η = 67%). But if it is necessary to work with high feed concentration, the use of 5 mm underflow diameter provides a rise in the efficiency. The HCO hydrocyclone was compared to the traditional family of hydrocyclones Rietema and presented advantages like higher efficiency (34% higher in average) and lower energy costs (20% lower in average). Finally, the efficiency curves and project equation have been raised for the HCO hydrocyclone each with satisfactory adjust.